Spatial Analysis of Determinants of COVID-19 Vaccine Hesitancy in Portugal - Pinto de Carvalho, Constança (2024)
Funding Information: This work was supported by the Portuguese Science Foundation (FCT) through the project SCOPE—Spatial Data Sciences for COVID-19 Pandemic (Grant DSAIPA/DS/0115/2020). M.R. and L.A. gratefully acknowledge the support of the CERENA (strategic project FCT-UIDB/04028/2020). M.R acknowledges FCT support for the research contract IST-ID/175/2018. This research was also partially supported by FCT grant DSAIPA/AI/0087/2018 to J.G.-S. and by PhD fellowship 2020.10157.BD to S.M. Publisher Copyright: © 2024 by the authors.